The κ⊥-factorization theorem for heavy flavour production at high energy - Catani, S; Ciafaloni, M; Hautmann, F (1991)
The κ⊥-factorization theorem is used to compute cross sections for heavy flavour production at high energy. The photoproduction and electroproduction cases are investigated in detail by resumming the leading behaviour to all orders in the QCD coupling constant. We show that the resummation procedure gives large correction factors with respect to lowest order calculations. © 1991.